Health status candidates for liver transplantation in the Western Brazilian Amazon - Soares, Gorete Simão; Israel, Jakeline de Lima; Genzini, Tércio; Prado, Patrícia Rezende do; Amaral, Thatiana Lameira Maciel (Brazilian Journal of Transplantation, 2013)
Purpose: To assess the health status of candidates for liver transplantation in a city of the Western Brazilian Amazon. Methods: Cross-sectional study with candidates for liver transplantation, living in Rio Branco, Acre, from August to October 2012. To obtain the data were structured interviews and clinical patient record with form containing sociodemographic data, status of health (physical and mental) and used the Hospital Anxiety and Depression scale and Quality of Life Brief (WHOQOLBref). The central tendency for continuous variables and absolute and relative frequency for dichotomous variables were performed. The analysis was performed using SPSS 17.0 software. Results: Most patients were men, 50.0% had more than 50 years of age and 57.1% of women had 31-50 years of age. The men had the highest average body weight compared to women; most had hepatitis B and MELD of 15, or 71.4% among women. As for comorbidities, gastritis accounted for 37.5% and hypertension 25.0%. Signs and symptoms were most commonly found edema of the lower limbs (75%) and ascites (62%). In the assessment of anxiety and depression using HADS, anxiety was observed in 12.5% of patients and depression in 37.5%. With regard to the quality of life of patients interviewed, according to domains of the WHOQOL-Bref, the lowest averages were observed in the environmental (average of 54.9 points) and physical (average of 55.1 points). However, when an individual examination areas, according to the lowest score score, the social sector had the lowest value in one of the interviewed patients (25 score points). Conclusion: The evaluation of the health status of liver transplant candidates of a city of the Western Brazilian Amazon found that these patients need care directed to the pre transplant overweight, as well as for gastritis comorbidities, hypertension and HBV should be controlled and treated, mental assistance for anxiety and depression and social support for waiting and being able to perform the liver transplant.